Missed nursing care, staffing, and patient falls - Kalisch, Beatrice J; Tschannen, Dana; Lee, Kyung Hee (Journal of nursing care quality, 2012)
Patient falls in hospitals continue to be a major and costly problem. This study tested the mediating effect of missed nursing care on the relationship of staffing levels (hours per patient day [HPPD]) and patient falls. The sample was 124 patient units in 11 hospitals. The HPPD was negatively associated with patient falls (r = -0.36, P < .01), and missed nursing care was found to mediate the relationship between HPPD and patient falls.